A ball-in-ball g-C3N4@SiO2 nano-photoreactor for highly efficient H2 generation and NO removal. Issue 16 (11th April 2017) - Lin, Bo; Chen, Sheng; Dong, Fan; Yang, Guidong
Abstract : A novel ball-in-ball structured g-C3 N4 @SiO2 nano-photoreactor was synthesized, which showed superior photocatalytic activity in hydrogen generation and in situ NO removal. Abstract : The design and construction of a nano-photoreactor with some complexity and elaborate functionalities is a novel and fascinating protocol to highly optimize the performances of a g-C3 N4 photocatalyst. Herein, a ball-in-ball structured g-C3 N4 @SiO2 composite nano-photoreactor was synthesized via a nanocasting technique combined with a partial etching technique, which showed diverse application potential in environmental protection and photocatalytic hydrogen evolution. As expected, the as-prepared nano-photoreactor exhibits a superior photocatalytic activity and excellent stability with respect to the above-mentioned aspects, and this enhanced performance could be attributed to its unique structural advantages of multiple scattering and reflecting effects, higher degree of crystallinity, and increased active surface area and porosity. More importantly, the nano-photoreactor provides a decent environment within nanoscale domains for catalytic reaction to greatly accelerate the conversion of reactants.